Effect of corrosive solutions on composites laminates subjected to low velocity impact loading - Mortas, Nurdane (2014)
In recent years, there has been a rapid growth in the use of fibre reinforced composite materials in engineering applications and this phenomenon will be continuing. In this context, composite structures can be exposed to a range of corrosive environments during their in-service life, which causes degradation in terms of material properties. Some works can be found in open literature, but the studies presented are not sufficient to establish a full knowledge about this subject. Therefore, the aim of this work is study the low velocity impact response of Kevlar/epoxy laminates and carbon/epoxy laminates, after immersion into hydrochloric acid (HCl) and sodium hydroxide (NaOH). The aggressive solutions affect significantly the impact strength, but their effects are strongly dependent of the concentration. On the other hand, a significant effect of the temperature can be found, independently of the aggressive solution, on the impact performance and residual bending strength.